OP0284 Impact of a Nurse Led Program of Patient Self-Assessment of Disease Activity on the Management of Rheumatoid Arthritis: Results of a Prospective, Multicentre, Randomized, Controlled Trial (Comedra). (23rd January 2014) - Dougados, M.; Perrodeau, E.; Fayet, F.; Gaudin, P.; Cerato, M.-H.; le Loet, X.; Flipo, R.-M.; Chabrefy, L.; Mouterde, G.; Euller-Ziegler, L.; Schaeverbeke, T.; Fautrel, B.; et al.
Abstract : Background: The current T2T and EULAR recommendations ( e.g. measures of disease activity must be obtained and documented regularly [1 ]. Nurses should promote self-management skills in order that patients might achieve a greater self efficacy and improvement [2 ]) are difficult to apply in daily practice Objectives: To evaluate the impact of a nurse led program of patient self-assessment of disease activity on the management of Rheumatoid Arthritis (RA). Methods: Study design : Prospective, randomized, controlled, open, 6-month trial (NCT #0131652). Participants 1/ Patients : Consecutive RA attending a clinic of the 20 participating centers were invited .2/ Nurses :all participated at a 1.5 day training session prior the start of the study. 3/ Treating rheumatologists : aware of the study but not of its primary objective. Study treatment : a program including: 1) a video explaining both the interest, calculation and interpretation of the DAS28-ESR, 2) Training of a self joint assessment, 3) A booklet and a calculator permitting the patient to report the results of his/her "auto" DAS28-ESR and to show the results to his/her treating rheumatologist. Treatment allocation :After written informed consent, the treatment was allocated randomly via en electronic system (e.g. either this above program or an evaluation of potential co-morbidities (not reported here). Outcome variables: Primary : percentage of patients with a change in DMARD therapy during the 6 months follow-up period. Other variables : changes in symptomatic parameters. Results: There was no difference in the baseline characteristics of the 970 recruited patients (488 and 482 in the active and control groups respectively): Age: 58±11 years, female gender: 79%, disease duration: 11[6.2-19.1] years, DAS28-ESR: 3.1±1.3, mHAQ: 0.25[0.00-0.62]; RAID: 2.7[1.3-4.3]. At the month 6 visit, the % patients bringing back a completed booklet was 89%. During the 6 months follow-up period, a DMARD therapy was changed in 17.2% vs. 10.9% in the active vs. control group ( p =0.0012) (OR=1.70 [1.17-2.19]). During the time of the study, there was no statistically significant inter-group differences (-0.10 [-0.10;0.3], p=0.41; -0.03 [-0.25; 0.18], p=0.761; -0.01 [-0.05; 0.04], p=0.806, in the DAS28-ESR, HAQ and RAID in the active vs . control group respectively. Conclusions: This study demonstrates the short term impact of a nurse leaded patient self assessment of RA disease activity program. Longer term follow up of patients is required to better evaluate the clinical benefit of this program References: Smolen J.S. et al ; Ann Rheum Dis 2010; 69, 631-7 Van Eijk-Hustings y. et al . Ann Rheum Dis. 2012; 71, 13-9 Acknowledgements: This study was conducted thanks to a grant from the French National Research Program ( PHRC) and thanks to an unrestricted grant from Roche Ltd France Disclosure of Interest: None Declared